The Role of SGLT2 Inhibitors in Atherosclerosis: A Narrative Mini-Review - Pahud de Mortanges, Aurélie; Salvador Jr., Dante; Laimer, Markus; Muka, Taulant; Wilhelm, Matthias; Bano, Arjola (Frontiers in Pharmacology, 2021)
Objective – Sodium glucose cotransporter 2 inhibitors (SGLT2-is) are antidiabetic drugs that improve glycemic control by limiting urinary glucose reuptake in the proximal tubule. SGLT2-is might suppress atherosclerotic processes and ameliorate the prognosis of patients with diabetes mellitus diagnosed with or at high risk of atherosclerotic cardiovascular disease (ASCVD). In this mini review, we examine the role of SGLT2-is in the development and progression of atherosclerosis throughout its spectrum, from subclinical atherosclerosis to ASCVD. Data Sources – PubMed and Google Scholar were searched for publications related to SGLT2-is and atherosclerosis. All types of articles were considered, including clinical trials, animal studies, in vitro observations, as well as reviews and meta-analyses. Data was examined according to its impact and clinical relevance. Synopsis of Content – We first review the underlying mechanisms of SGLT2-is on the development and progression of atherosclerosis, including favourable effects on lipid metabolism, reduction of systemic inflammation, as well as improvement of endothelial function. We then discuss the putative impact of SGLT2-is on the formation, composition, and stability of atherosclerotic plaque. Furthermore, we evaluate the effects of SGLT2-is in subclinical atherosclerosis assessed by carotid intima media thickness and pulse wave velocity. Subsequently, we summarize the effects of SGLT2-is in ASCVD events, including ischemic stroke, angina pectoris, myocardial infarction, revascularization, and peripheral artery disease, as well as adverse cardiovascular events. Moreover, we examine factors that could modify the role of SGLT2-is on atherosclerosis, including sex, age, diabetes, glycemic control, ASCVD, and SGLT2-i compounds.